2018
DOI: 10.1073/pnas.1810729116
|View full text |Cite
|
Sign up to set email alerts
|

SENCRstabilizes vascular endothelial cell adherens junctions through interaction with CKAP4

Abstract: SENCR is a human-specific, vascular cell-enriched long-noncoding RNA (lncRNA) that regulates vascular smooth muscle cell and endothelial cell (EC) phenotypes. The underlying mechanisms of action of SENCR in these and other cell types is unknown. Here, levels of SENCR RNA are shown to be elevated in several differentiated human EC lineages subjected to laminar shear stress. Increases in SENCR RNA are also observed in the laminar shear stress region of the adult aorta of humanized SENCR-expressing mice, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 47 publications
0
71
0
Order By: Relevance
“…SENCR positively regulated angiogenic processes in HUVECs [60], and was further found to be induced by laminar shear stress in human ECs [61]. Knockdown of SENCR displaced CKAP4 (Cytoskeletal-associated protein 4), which then bound CDH5 (Cadherin 5), destabilizing the CDH5/CTNND1 (Catenin delta 1) complex and perturbing EC adherens junctions [61]. SENCR has not yet been directly linked to AA disease, but the proposed mechanisms in SMCs and ECs make it an intriguing lncRNA for further exploration in disease-relevant models.…”
Section: Sencrmentioning
confidence: 89%
See 1 more Smart Citation
“…SENCR positively regulated angiogenic processes in HUVECs [60], and was further found to be induced by laminar shear stress in human ECs [61]. Knockdown of SENCR displaced CKAP4 (Cytoskeletal-associated protein 4), which then bound CDH5 (Cadherin 5), destabilizing the CDH5/CTNND1 (Catenin delta 1) complex and perturbing EC adherens junctions [61]. SENCR has not yet been directly linked to AA disease, but the proposed mechanisms in SMCs and ECs make it an intriguing lncRNA for further exploration in disease-relevant models.…”
Section: Sencrmentioning
confidence: 89%
“…SENCR also correlated with the expression of the FIL1 (Friend Leukemia Integration virus 1) gene [59], a crucial regulator in EC function and specification. SENCR positively regulated angiogenic processes in HUVECs [60], and was further found to be induced by laminar shear stress in human ECs [61]. Knockdown of SENCR displaced CKAP4 (Cytoskeletal-associated protein 4), which then bound CDH5 (Cadherin 5), destabilizing the CDH5/CTNND1 (Catenin delta 1) complex and perturbing EC adherens junctions [61].…”
Section: Sencrmentioning
confidence: 99%
“…We hypothesize that upregulation of PICART1 may also suppress proliferation and induce apoptosis in ZIKV-infected human TEC, as shown by other authors that this lncRNA impairing proliferation 42 and inducing apoptosis 43 in lung cancer cells. Another lncRNA, SENCR can stabilize the vascular endothelial cell adherent junctions 44 , which mediate cell adhesion and intracellular signals 45 . Accordingly, the upregulation of SENCR may be involved in regulating the enhancement of cell adhesion seen in ZIKV-infected TEC.…”
Section: Discussionmentioning
confidence: 99%
“…Functional tests confirmed that SENCR overexpression significantly inhibited cell proliferation and migration. Besides, SENCR not only regulates the function of VSMCs but stabilizes the adhesion and connection of vascular ECs through interaction with CKAP4 (Lyu et al, 2019). Moreover, SENCR identified is involved in regulating the differentiation of ECs into pluripotent cells and controlling the angiogenic capacity of HUVEC (Boulberdaa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%